Evaluation of different detection methods of biofilm formation in the clinical isolates - Hassan,Afreenish (2011)
BACKGROUND: Microorganisms growing in a biofilm are associated with chronic and recurrent human infections and are highly resistant to antimicrobial agents. There are various methods to detect biofilm production like Tissue Culture Plate (TCP), Tube method (TM), Congo Red Agar method (CRA), bioluminescent assay, piezoelectric sensors, and fluorescent microscopic examination. OBJECTIVE: This study was conducted to compare three methods for the detection of biofilms. METHOD: The study was carried out at the Department of Microbiology, Army Medical College, National University of Sciences and Technology, Pakistan, from January 2010 to June 2010. A total of 110 clinical isolates were subjected to biofilm detection methods. Isolates were identified by standard microbiological procedures. Biofilm detection was tested by TCP, TM and CRA. Antibiotic susceptibility test of biofilm producing bacteria was performed by using the Kirby-Bauer disc diffusion technique according to CLSI guidelines. RESULTS: The TCP method was considered to be superior to TM and CRA. From the total of 110 clinical isolates, TCP method detected 22.7% as high, 41% moderate and 36.3% as weak or non-biofilm producers. We have observed higher antibiotic resistance in biofilm producing bacteria than non-biofilm producers. CONCLUSION: We can conclude from our study that the TCP method is a more quantitative and reliable method for the detection of biofilm forming microorganisms as compared to TM and CRA methods, and it can be recommended as a general screening method for detection of biofilm producing bacteria in laboratories.